HIJANETICS (HIJAIYAH AND ENGLISH PHONETICS) IN EFL PRONUNCIATION CLASSES: A PARTICIPATORY ACTION RESEARCH - Wati, Shafrida (UPT. Pengembangan Bahasa IAIN Zawiyah Cot Kala Langsa, 2019)
This study explored the use of sounds association of Hijaiyah (Arabic Alphabets) and English phonetics (HIJANETICS) in teaching pronunciation to students who learn English as a Foreign Language, especially in Aceh context. It aimed at overcoming the learners’ difficulties in producing English sounds, enhancing their communicative competency, and also promoting an alternative approach to teach pronunciation for teachers. The researcher worked with four English teachers of Madrasah Ulumul Quran (MUQ) Langsa, Aceh Province, whom were selected purposively. Observation and in-depth interview were conducted to obtain the results of the research. The findings revealed that phonetics training by associating the sounds to Hijaiyah (Arabic Alphabets) improved some learners’ pronunciation qualities, which were clearer and understandable. It promoted independent learning for the students since their ability to recognize phonetics symbols allow them to discover how a word is pronounced. Most importantly, it engaged and motivated them to learn the foreign language.